Effects of Arts and Psychomotor Therapies in Personality Disorders. Developing a Treatment Guideline Based on a Systematic Review Using GRADE - Haeyen, Suzanne (Frontiers in Psychiatry, 2022)
What is the effect of arts and psychomotor therapies, using art, dance, drama, music, movement and body awareness, in personality disorder treatment? This was explored by developing a treatment guideline based on a systematic review using the GRADE system within the context of the Dutch national multidisciplinary guidelines for treatment of personality disorders. Conclusions were formulated by a work group and based on the scientific substantiation and were integrated with other indications in the functioning of arts and psychomotor therapies in personality disorders. The first general search yielded 1900 records which was brought back to 53 full-texts. Ultimately, 1 RCT and 2 pilot studies were included. Recommendations for treatment are that arts and psychomotor therapies are included in treatment, independent of age, sex or specific diagnostic characteristics. Arts and psychomotor therapies can be considered for purposes of coming into emotional contact with difficult aspects of patients and their experiences, to work on goals such as regulation of emotions, stress, identity/self-image, self-expression, mood/anxiety, relaxation, changing patterns and social functioning. Enlisting arts and psychomotor therapies for patients with a personality disorder is recommended because they value these therapies and perceive these to be effective. It could be considered to ask arts and psychomotor therapies to provide a contribution to the diagnostic process, to the problem analysis via observation and to determining treatment indication and treatment goals. More research is needed.